Kinase Inhibition in Relapsed/Refractory Leukemia and Lymphoma Settings: Recent Prospects into Clinical Investigations - Caio Bezerra Machado; Flávia Melo Cunha de Pinho Pessoa; Emerson Lucena da Silva; Laudreísa da Costa Pantoja; Rodrigo Monteiro Ribeiro; Manoel Odorico de Moraes Filho; Maria Elisabete Amaral de Moraes; Raquel Carvalho Montenegro; Rommel Mário Rodriguez Burbano; André Salim Khayat; Caroline Aquino Moreira-Nunes (MDPI AG, 2021)
Cancer is still a major barrier to life expectancy increase worldwide, and hematologic neoplasms represent a relevant percentage of cancer incidence rates. Tumor dependence of continuous proliferative signals mediated through protein kinases overexpression instigated increased strategies of kinase inhibition in the oncologic practice over the last couple decades, and in this review, we focused our discussion on relevant clinical trials of the past five years that investigated kinase inhibitor (KI) usage in patients afflicted with relapsed/refractory (R/R) hematologic malignancies as well as in the pharmacological characteristics of available KIs and the dissertation about traditional chemotherapy treatment approaches and its hindrances. A trend towards investigations on KI usage for the treatment of chronic lymphoid leukemia and acute myeloid leukemia in R/R settings was observed, and it likely reflects the existence of already established treatment protocols for chronic myeloid leukemia and acute lymphoid leukemia patient cohorts. Overall, regimens of KI treatment are clinically manageable, and results are especially effective when allied with tumor genetic profiles, giving rise to encouraging future prospects of an era where chemotherapy-free treatment regimens are a reality for many oncologic patients.